Comparetive field performances and quality of conventional combine and mid-size combine in wetland rice cultivation in Malaysia - Elsoragaby, Suha Gaafar Babekir; Yahya, Azmi; Ahmed, Modather Mairghany Abdin; Adam, Nor Mariah; Mahadi @ Othman, Muhammad Razif; Mat Nawi, Nazmi; Mat Su, Ahmad Suhaizi (Malaysian Society of Agricultural Engineers, 2019)
In paddy cultivation, harvesting is the most important operation, which needs suitable machinery. Thus, this study was carried out to compare and evaluate field performances, grain quality and harvesting grain losses of conventional 5 m cutting width NEW HOLLAND CLAYSON 8080, combine running on a total net area of 42.78 hectares and the new midsize 2.7 m cutting width WORLD STAR WS7.0, combine running on a total net area of 16.95 hectares of plots for two rice (Oryza sativa L.) cultivation seasons. The conventional combine as compared to mid-size combine showed 14.4% greater mean fuel consumptions, 31.1% greater mean effective field capacity, 20.90% lesser mean operational speed and 10.8% lesser mean field efficiency. In terms of quality of harvested grain the conventional combine showed 9.48% lesser mean whole and healthy grain and 2.29 times greater mean broken grain and 85.78% greater mean foreign materials and 8.97 times greater mean empty grain than the mid-size combine. In terms of grain losses, the conventional combine showed 2.06 times greater mean total losses, 2.94 times greater mean cleaning losses, 1.03 times greater mean unthreshed losses than the mid-size combine. The results revealed that the mid-size combine is more suitable in conducting the harvesting operation in rice cultivation in Malaysia than the conventional combine.